The Influence of New Colored Light Stimulation Methods on Heart Rate Variability, Temperature, and Well-Being: Results of a Pilot Study in Humans. (28th November 2013) - Litscher, Daniela; Wang, Lu; Gaischek, Ingrid; Litscher, Gerhard
Abstract : Changes of light intensity of different colors can shift many physiological parameters and conditions like melatonin, alertness, body temperature, heart rate (HR), and heart rate variability (HRV). The aim of this pilot study was to investigate acute temperature, HR, HRV, and state of mind reactivities after illumination with red (631 nm) and blue (456 nm) light (illuminance 140 lux for both). Seven healthy volunteers (5 females, 2 males; mean age ± SD 34.1 ± 11.9 years) were investigated at the Medical University of Graz, using new color light panels. Significant decreases were found only after 10 min blue light stimulation in nose temperature (P = 0.046 ), HR (P < 0.05 ), and total HRV (P = 0.029 ), in association with a significant alteration of the emotional state (stress level score, P = 0.006 ). However, red light stimulation of the same persons did not induce the same effects in these parameters. The effect of blue light as environmental stimulation on human health is not clarified in detail and needs further investigations.